2022
DOI: 10.1515/reveh-2021-0139
|View full text |Cite
|
Sign up to set email alerts
|

A review on chromium health hazards and molecular mechanism of chromium bioremediation

Abstract: Living beings have been devastated by environmental pollution, which has reached its peak. The disastrous pollution of the environment is in large part due to industrial wastes containing toxic pollutants. The widespread use of chromium (Cr (III)/Cr (VI)) in industries, especially tanneries, makes it one of the most dangerous environmental pollutants. Chromium pollution is widespread due to ineffective treatment methods. Bioremediation of chromium (Cr) using bacteria is very thoughtful due to its eco-friendly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 197 publications
0
3
0
Order By: Relevance
“…In another study, edaphic cyanobacteria were tested for Cr remediation and it was found that these bacteria produce polysaccharides, glycoproteins, lipopolysaccharides, and ionic functional groups that can coordinate with Cr and reduce its availability ( Cheung and Gu, 2007 ). Moreover, different Cr-tolerant bacteria including Bacillus , Enterobacter , Pseudomonas , and Streptomyces have been identified and they can remove the Cr by 50-90% ( Ramesh and Winkler, 2010 ; Bansal et al., 2019 ; Elahi and Rehman, 2019 ; Murthy et al., 2022 ). The study findings of Wen et al.…”
Section: Microbial Mediated Remediation Of Chromium Contaminated Soilsmentioning
confidence: 99%
“…In another study, edaphic cyanobacteria were tested for Cr remediation and it was found that these bacteria produce polysaccharides, glycoproteins, lipopolysaccharides, and ionic functional groups that can coordinate with Cr and reduce its availability ( Cheung and Gu, 2007 ). Moreover, different Cr-tolerant bacteria including Bacillus , Enterobacter , Pseudomonas , and Streptomyces have been identified and they can remove the Cr by 50-90% ( Ramesh and Winkler, 2010 ; Bansal et al., 2019 ; Elahi and Rehman, 2019 ; Murthy et al., 2022 ). The study findings of Wen et al.…”
Section: Microbial Mediated Remediation Of Chromium Contaminated Soilsmentioning
confidence: 99%
“…Studies have shown that a concentration Cr(III) in culture medium and concentrations of Cr(VI) in soil limit the germination of seeds of plant species [ 3 ]. Likewise, it has been determined that Damage to DNA, in human being, may be caused by Cr (VI) at and Cr (III) at [ 4 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the aforementioned waste management strategy is particularly important regarding soils contaminated with chromium, including Cr(VI), whose strong oxidizing properties make it a cancerous and mutagenic element for living organisms, and which is therefore considered as a priority contaminant by the US Environmental Protection Agency (USEPA) [27]. The major anthropogenic sources of this element in nature are electroplating; steel fireproofing; the broadly understood chemical industry, including the synthesis of chemicals for wood preservation, production of paints, textile dyes, glues, and catalysts [28,29]; and also tanning, which interferes severely with the natural environment [30].…”
Section: Introductionmentioning
confidence: 99%